PENERAPAN LITERASI INTEGRATIF UNTUK MENINGKATKAN PEMAHAMAN PEMBELAJARAN KEAGAMAAN DI MADRASAH - Nuzmi Sasferi (EDU RESEARCH, 2024)
Good literacy skills will help someone understand both oral and written information. These competencies can support each other if someone can master literacy and can sort information that can support the success of their lives. Reading literacy has a very important role in religious learning in madrasas, first, reading literacy allows access to various secondary literature such as the Koran, tafsir, and academic studies which can enrich a person's understanding of religious teachings, second, reading literacy skills encourage students' critical and analytical thinking in religious learning. The aim of this research is to determine strategies for implementing reading literacy in increasing understanding of religious learning in madrasas.